The comprehensive effects of high-sensitivity C-reactive protein and triglyceride glucose index on cardiometabolic multimorbidity - Wan, Bingen; Wang, Silin; Hu, Sheng; Han, Weiqing; Qiu, Shengyu; Zhu, Lingxiao; Ruan, Liancheng; Wei, Yiping; Xu, Jianjun (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose index (TyG index) is one of the surrogate markers of insulin resistance, and high-sensitivity C-reactive protein (hsCRP) reflects systemic inflammation. Existing studies suggest that insulin resistance or systemic inflammation may be indicative of cardiometabolic disease, but few of the existing studies have combined the TyG index and inflammation levels before assessing cardiometabolic multimorbidity. Our study data came from the China Health and Retirement Longitudinal Study (CHARLS). Participants in this data were followed for 9 years, and we used these data to conduct a long-term analysis to assess the combined effects of the TyG index and hsCRP on cardiometabolic multimorbidity in Chinese adults over 45 years of age.PurposeTo study the combined effect of TyG index and hsCRP on cardiometabolic multimorbidity in middle-aged as well as elderly Chinese.MethodThe study data came from the China Health and Retirement Longitudinal Study (CHARLS), which included a total of 4,483 middle-aged and elderly participants who did not have cardiovascular metabolic diseases at baseline, which was from CHARLS 2011, and the last survey was in 2020. A total of five cardiometabolic diseases were considered in this study: diabetes, hypertension, hyperlipidemia, heart disease and stroke. A person was defined as having cardiometabolic multimorbidity when he/she had two or more cardiometabolic diseases at the same time. TyG index (median as cut-off) and hsCRP (1mg/L as cut-off) were each divided into two groups and combined into four groups (Group L-L: TyG index<median & hsCRP<1mg/L; Group H-L: TyG index>=median & hsCRP<1mg/L; Group L-H: TyG index<median & hsCRP>=1mg/L; Group H-H: TyG index>=median & hsCRP>=1mg/L). Multiple regression equations were fitted to analyse the combined influence of TyG index and hsCRP on cardiometabolic multimorbidity.ResultsTyG index increases the risk of CMM events independently of hsCRP, as does the reverse. When the TyG index is elevated and hsCRP is also elevated, this condition significantly increases the danger of cardiometabolic multimorbidity in middle-aged and elderly Chinese.ConclusionHigh levels of TyG index and hsCRP can enhance the danger of cardiometabolic multimorbidity in Chinese middle-aged and elderly people, and the joint use of hsCRP and TyG index assessment may be a better way to achieve primary prevention of cardiometabolic multimorbidity in Chinese middle-aged and elderly people.